Beetles (Coleoptera) associated with the tinder fungus, Fomes fomentarius (L.) Fr. (Polyporales: Polyporaceae) in Ukraine - Drogvalenko, O. M. (The Kharkiv Entomological Society Gazette, 2023)
The tinder fungus Fomes fomentarius is one of the most common species of xylotrophic fungi, found both in natural and anthropogenic biotopes. The fungi have perennial fruiting bodies with dense but not very hard textured ‘tissues’ and are the center of a stable complex of mycetophilous insects, mainly beetles. A study in Ukraine found 110 species of beetles from 26 families on/in carpophores, of which 72 species turned out to be mycetobionts. It was found that, regardless of the location of the study, the specialist species complex remains constant: Tenebrionidae — Ciidae (Cis spp. from the castaneus species group) — Ciidae (Ropalodontus spp.) — Ptinidae (Dorcatoma spp.). 2 figs, 1 tab., 23 refs.
Keywords: mycetobionts; mycetophages; bracket fungi; fruiting body